Pendidikan Politik Kebangsaan Berbasis Pesantren - Romy Hermawan; Rispa Ngindana (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2020)
Islamic boarding school as a social institution that experiences dialectics both inside and outside the boarding school which is a projection of the boarding school community itself. The role of Islamic boarding schools which initially focused on character and religious education, now forces them to make changes internally such as the education system, social construction and public and religious education providers including political education. The purpose of this activity is to increase awareness of the importance of political education for students, increase understanding of political education in contrast to politics for students and increase understanding of the importance of political education as an effort to educate students as NKRI people who embrace the Pancasila Democracy. This community service method uses a social approach by analyzing the situation of khalayk or certain organizations, namely santri. The results of this activity show the understanding of the students of Miftahul Ulum Islamic Boarding School, Mentaraman Village, Donomulyo District initially argued that political behavior is bad behavior, but after it was conveyed that so far in daily life political behavior has been unconsciously realized. With this activity in the form of national political education it is hoped that it can increase students 'knowledge about national politics, in addition it is expected to further increase students' awareness that politics is not negative behavior.